PENGARUH MOTIVASI KERJA, BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN CV JADE INDOPRATAMA MALANG - Rizky Anshary; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis study aims to examine and analyze the effect of work motivation, organizational culture and work environment on the performance of CV employees. Jade Indo Pratama Malang both partially and together. The population is 130 employees and a sample of 40 people. Data collection through questionnaires. Data analysis in this study uses SPSS version 16. The sampling technique using quantitative methods and data testing techniques used in this study include validity test, reliability test, classic assumption test and multiple linear regression analysis, and testing the research hypothesis.The results of the analysis show that partially organizational culture does not have a significant effect on employee performance and work environment does not significantly influence employee performance while work motivation has a significant effect on employee performance. Together, it shows that work motivation, organizational culture and work environment significantly influence employee performance.Keywords: work motivation, organizational culture,  work environment and employee performance